Women Workers Resistance Against Elite Class Hegemony in Indonesia - KUSUMASARI, BEVAOLA; UMAR, SUYULATUDZ (Universitas Muhammadiyah Yogyakarta, 2018)
This study describes the women carrier labor resistance movement in Yogyakarta towards the dominance and hegemony done by other classes in the social structure of the market environment. This study uses a qualitative method with phenomenological approach and data analysis refering to the concept of qualitative data analysis. The results showed that the social structure in a market environment puts the women in the lowest social class and becoming the most effective tool in pursuing the domination and hegemony of the dominant actors. As a result, the market does not provide space for women workers to participate in the production process. They can not play a role in the social change because their position can only be regarded as a second class causing the increasingly unequel gap between the social classes. These conditions can then encourage the emergence of the women carrier labor activists to reduce disparities through alternative media.